The influence of communication and student engagement on higher order thinking skills in automotive vocational education - Ibnu Siswanto; Purwanto Purwanto; Saian Nur Fajri; Ridho Azahar (Jurnal Pendidikan Vokasi, 2025)
Higher order thinking skills (HOTS) are essential in vocational and engineering education; however, empirical evidence explaining how communication and student engagement jointly shape the development of HOTS remains limited, particularly in automotive contexts. This study aims to examine the partial and simultaneous influence of communication and student engagement on students’ HOTS, including problem-solving, critical thinking, and creativity. An ex post facto quantitative correlational design was employed, involving 208 undergraduate and diploma students from the Automotive Engineering Education and Vocational programs at Universitas Negeri Yogyakarta. Data were collected using validated questionnaires, and multiple linear regression analysis was conducted to determine both independent and combined effects of the predictor variables. The findings reveal that communication and student engagement each exert a positive and significant influence on HOTS, while their simultaneous contribution explains 71.9% of the variance in students’ HOTS scores. These results indicate that students who actively communicate, participate, and engage cognitively, behaviorally, emotionally, and agentically demonstrate stronger analytical, reflective, and creative thinking abilities. The study confirms that communication and engagement are not merely supporting attributes, but key drivers of advanced cognitive development in automotive vocational education. Implications highlight the importance of designing interactive and collaborative learning environments that foster participation and meaningful academic involvement to prepare students for increasingly complex professional challenges.